The health economic benefits of perioperative patient warming for prevention of blood loss and transfusion requirements as a consequence of inadvertent perioperative hypothermia. Issue 9 (September 2018) - Ingram, Andy; Harper, Mark
Active warming of patients is recommended by The National Institute for Health and Care Excellence (NICE) to prevent inadvertent perioperative hypothermia (IPH). This paper examines the cost effectiveness of one consequence of IPH, an increase in blood loss and the resulting transfusion risk. We quantified the risk and modelled two patient pathways, one with and one without warming, across two different surgery types. We were able to demonstrate the cost effectiveness of active warming based on one consequence even allowing for uncertainties in the model.